Clinical and angiographic characteristics of very young patients undergoing invasive coronary angiography - Xing Hu; Xuefeng Wang; Kerui Huang; Yi Zhong; Yong Luo; Ji Li; Yuanmin Hu (Frontiers in Cardiovascular Medicine, 2026)
Background Atherosclerotic risk factors are increasingly prevalent among younger populations, contributing to a rise in premature coronary artery disease. This study aims to investigate the clinical and angiographic characteristics of this specific demographic. Methods This retrospective study enrolled 215 consecutive patients aged 35 years or younger (181 men) who underwent coronary angiography (CAG) at our center. Clinical data and angiographic images were collected and analyzed. Independent predictors of ischemic heart disease (IHD) were evaluated using logistic regression analysis. Discriminative performance was assessed using receiver operating characteristic curve analysis. Results In the selected cohort of 215 young patients, the prevalence rates of obesity/overweight, smoking, dyslipidemia, hypertension, and diabetes mellitus were 56.7%, 53.0%, 31.2%, 23.3%, and 8.4%, respectively. Within this cohort, 92 (42.8%) patients exhibited various forms of IHD, with 85.9% of cases attributed to atherosclerotic cause and 14.1% attributed to nonatherosclerotic etiologies. A total of 202 (94.0%) patients underwent CAG due to chest pain, ischemic electrocardiogram changes, and/or elevated high-sensitivity cardiac troponin T (hs-cTn T) levels. IHD prevalence was highest at 73.8% for those with all three indications, compared to 44.1% with two, and 9.2% with one or none (all p < 0.001). Multivariate logistic regression analysis identified diabetes mellitus (odds ratio [OR], 14.71; 95% confidence interval [CI], 1.59-135.76; p = 0.018), ischemic electrocardiogram changes (OR, 3.11; 95% CI, 1.09-8.91; p = 0.034), interventricular septum thickness (OR, 1.46; 95% CI, 1.08-1.98; p = 0.015), and elevated hs-cTn T levels (OR, 8.26; 95% CI, 3.17-21.51; p < 0.001) as independent predictors of IHD. The combined multivariable model demonstrated a robust discriminative performance (AUC, 0.85; 95% CI, 0.79-0.90; p < 0.001). Conclusions The present study demonstrated a significant prevalence of modifiable atherosclerotic risk factors among very young patients undergoing CAG. Although atherosclerosis was identified as the primary cause of IHD, nonatherosclerotic etiologies also contributed substantially. The presence of two or more angiographic indications—namely, chest pain, ischemic electrocardiogram changes, and/or elevated hs-cTn T levels—was associated with an increased risk of IHD. Furthermore, diabetes mellitus, ischemic electrocardiogram changes, interventricular septum thickness, and elevated hs-cTn T levels were independent predictors of premature IHD.